Semantic web developments in Hungarian public collections in an international perspective - Marton Nemeth (Libellarium: Journal for the Research of Writing, Books, and Cultural Heritage Institutions, 2017)
In my paper after describing the international context of the Hungarian semantic web projects, I would like to introduce the semantic web project of the Hungarian National Széchényi Library. They built up an ontology published their catalogue and authority data as linked open data on the semantic web (by the help of an own name space, SKOS and VIAF). They also generated a SPARQL-endpoint in order to put their semantic datasets to the cloud. A recent project of the Petőfi Literary Museum focusing on name authority record. They are converting around 620000 authority record into RDF-XML format. They would like to publish their data in VIAF (worldwide semantic virtual authority file database) and make them accessible on the OCLC WorldCat semantic environment. This database will be the second database followed by the Hungarian National Library that will appear in VIAF. They are planning also to build up an own triple-store in collaboration with other Hungarian libraries and museums in order to enrich their own semantic datasets with external semantic links. In this context I would like to introduce the tools developed by the framework of the ALIADA project with an international collaboration in order to offer a complete environment to public collection to help them appearing on the semantic web with their own triple-store and datasets. I would like to describe some major projects in semantic field in Hungary that can be implemented possibly in the future. I will mainly highlight the concept of the Hungarian National Namespace that can set all the institutional efforts from public collections to a common framework. Last but not least I would like to describe the use of microformats (based on HTML 5 standard) to put semantic markup data elements into full-text online content resources. That can be also really relevant for public collections (especially for libraries) in order to provide new semantic datasets based on their existing full-text online resources.